Role of Direct Antiviral Agents in Treatment of Chronic Hepatitis C Infection in Renal Transplant Recipients - Sourabh Sharma; Debabrata Mukherjee; Ranjith K. Nair; Bhaskar Datt; Ananth Rao (Journal of Transplantation)
Background. Since the introduction of direct antiviral agents (DAAs), morbidity of HCV has considerably decreased but still no guidelines have been formulated in renal transplant recipients (RTRs). We studied efficacy and tolerability of direct antiviral agents in RTRs. Methods. This prospective observational study was conducted at Army Hospital Research & Referral, Delhi, from June 2016 to May 2017. Forty-five HCV infected RTRs with stable graft function were included. Results. Median time between renal transplantation and the start of anti-HCV therapy was 36 months (1–120 months). The majority (66.7%) were infected with genotype 3. Baseline median HCV RNA level was 542648 IU/ml (1189–55028534 IU/ml). Sofosbuvir-Ribavirin combination (24 weeks) was given to 30 patients including 3 cirrhotics, Ledipasvir-Sofosbuvir combination to 8 patients, and Daclatasvir-Sofosbuvir combination to 7 patients, including 2 cirrhotics. Rapid virological response was observed in 29 patients treated with Sofosbuvir/Ribavirin, all 8 patients on Sofosbuvir/Ledipasvir, and all 7 patients on Sofosbuvir/Daclatasvir. End treatment response and sustained virological response (12 weeks) were achieved in all patients irrespective of genotype or treatment regimen. Decrease in mean HCV RNA level and transaminase level was statistically significant (p<0.01). Ribavirin was significantly associated with anaemia (p=0.032). Conclusions. DAA regimens are well tolerated and highly efficacious. Response to DAA is good irrespective of genotype, drug combination, initial HCV RNA level, age or sex of patient, or graft age. However, Sofosbuvir/Ledipasvir and Sofosbuvir/Daclatasvir combination is preferable.